Endoglin Expression (CD105) in Ephithelial Ovarian Cancer: Ekspresi Endoglin (cd105) Pada kanker Ovarium Tipe Epitelial - Rizkinov Jumsa; John Rambulangi; Sharvianty Arifuddin; Upik Miskad (Indonesian Socety of Obstetrics and Gynecology, 2018)
Abstract Objective: Endoglin ( CD105 ) is one of the factors that play a role in vascular development , angiogenesis and vascular homeostasis. The aim of this research is to address the endoglin expression (CD105) in primary tumor and metastasis tumor (omentum) and their relation with clinicopathological factor: stadium, differentiation level, and histological epithelial ovarian cancer. Method: The research was performed at Public Service Hall of Dr. Wahidin Sudirohusodo Hospital and educational networking hospital of Obstetrics and Gynecology Departement of Medical Faculty Hasanuddin University Makassar. The research design is cross sectional with 55 samples consisting of 55 samples of primary tumor and 55 matastasis tumor. Imunohistochemistry examination was performed to all samples. Result:The results show a significant relation between endoglin (CD105) at omentum metastasis tumor and stadium and cell differentiation level of epithelial ovarian cancer. There is no significant relation between endoglin (CD105) expression at primary tumor of ovarian cancer and stadium and differentiation and type of histopathological cell. In addition, there is no significant relation between endoglin expression (CD105) at omentum metastasis tumor and type of histophatological cell of ovarian cancer. There is a significant correlation (strong category) between endoglin expression at omentum metastasis tumor and endoglin expression at primary tumor of epithelial ovarian cancer. Conclusion: Endoglin expression in ovarian cancer metastatic tumor to omentum is correlated to clinical stage and differentiation level of ovarian cancer. And endoglin is one of the pro angiogenic and pro metastasis factors. Keywords:epithelial ovarian cancer, endoglin expression, CD105, immunohistochemistry